2017
DOI: 10.1063/1.4993201
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low turn-on voltage and on-resistance vertical GaN-on-GaN Schottky power diodes with high mobility double drift layers

Abstract: This letter reports the implementation of double-drift-layer (DDL) design into GaN vertical Schottky barrier diodes (SBDs) grown on free-standing GaN substrates. This design balances the trade-off between desirable forward turn-on characteristics and high reverse breakdown capability, providing optimal overall device performances for power switching applications. With a wellcontrolled metalorganic chemical vapor deposition process, the doping concentration of the top drift layer was reduced, which served to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 37 publications
(49 reference statements)
2
47
0
Order By: Relevance
“…The integrated SBD in this work was benchmarked against state-of-the-art vertical SBDs on silicon, sapphire and GaN substrates in Fig. 5, revealing state-of-the-art performance compared to vertical GaN-on-Si SBDs [17], [18], [27][28][29][30][31][32][33][34][35][36][37][38]. The V BR of the integrated MOSFET-SBD can be significantly improved: 1.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The integrated SBD in this work was benchmarked against state-of-the-art vertical SBDs on silicon, sapphire and GaN substrates in Fig. 5, revealing state-of-the-art performance compared to vertical GaN-on-Si SBDs [17], [18], [27][28][29][30][31][32][33][34][35][36][37][38]. The V BR of the integrated MOSFET-SBD can be significantly improved: 1.…”
Section: Resultsmentioning
confidence: 86%
“…The V BR of the integrated MOSFET-SBD can be significantly improved: 1. By using low-defect-density GaN substrates [27], [29], [30]; 2. By increasing the drift layer thickness and further reducing the background carrier concentration from 2×10 16 cm -3 in this work to ~10 15 cm -3 [30], [31]; 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, the samples were annealed at a certain condition to further improve the ohmic behavior. (Ti/Al/Ni/Au at 600-840 • C in N 2 for 20-30s [2,26,29,33,65,67,71,72]; Ti/Al/Pt/Au at 700 • C-850 • C in N 2 for 30s [5,53,54,86]; Ti/Al [19,31,37,38,68,75,76,82]; Ti/Al/Ti/Au [32,67,83,87]; Ti/Al/Au [18,81].) Then, the nickel layer is formed on ohmic contact metal by an electroplating process, as shown in Figure 11b.…”
Section: Fabrication Steps Of Vertical Gan Sbdsmentioning
confidence: 99%
“…It was reported that the structure greatly reduced the on-state resistance [36]. Fu et al made further improvement to MOCVD regrown drift layers on HVPE substrate by introducing double-drift-layer (DDL) design [37]. An additional moderately doped GaN layer was inserted in between the lightly doped top layer and the highly doped bottom layer.…”
Section: Gan Substrate Growth and Epitaxial Structure Optimizationmentioning
confidence: 99%